How to survive a disaster earthquakes, floods, fires, airplane crashes, terrorism and much more - Stilwell, Alexander (AMBER Books LTD, 2017)
What do you do if your aircraft ditches in the sea? Or your building is on fire? Or you are the victim of a terrorist attack? Would you make the right decision to save yourself and the lives of others? How to Survive a Disaster is a complete handbook to any crisis that may suddenly arise, from food or water shortages, to natural disasters, to plane crashes and hostage situations. A crisis might last a few hours, days, or even years - with this book you can be ready for any eventuality. With tips and techniques from survival experts, the book is divided into two main sections. The first four chapters deal with learning how to prepare yourself best for disaster. These chapters cover mental strength, physical strength, first aid skills and useful equipment and how to use it, so that if you find yourself in a crisis, you're ready. The second section of the book deals with different crisis situations you may face, such as harsh climates and terrains, natural disasters such as floods and forest fires, manmade disasters such as plane crashes and power failures, and terrorist attacks and/or hostage situations. In each chapter scenarios are explored and expert tips given, both on what to do in the moments and hours after disaster has struck, but also in the weeks and months that follow. With more than 300 easy-to-follow artworks and handy pull-out lists of key information, How to Survive a Disaster is the definitive crisis survival guide for anyone wanting to be ready for anything - it could literally save your life.